The walk [large type] - Evans, Richard Paul (Evans, Richard Paul. Walk, 2010)
What would you do if you lost everything--your job, your home, and the love of your life--all at the same time? When it happens to Seattle ad executive Alan Christoffersen, he's tempted by his darkest thoughts but then decides to take a walk, heading for the farthest point on his map: Key West, Florida. The people he encounters along the way, and the lessons they share with him, will save his life.